Pola Interaksi Anak Perempuan dengan Ayah Tiri di Kelurahan Kijang Kota Kecamatan Bintan Timur Kabupaten Bintan - Sinta Oktaviani; Emmy Solina; Rahma Syafitri (Social Issues Quarterly, 2023)
The Convention on the Rights of the Child has been ratified by the State of the Republic of Indonesia through Presidential Decree Number 36 of 1990 concerning the basic rights of the child. Not only tha state, but also the family obliged to fulfill the right of the child. In fact, each family certainly has its own conflicts which ultimately cause debate and end up with the path of divorce as for the efforts made by parent to fulfill the rights of children when their family is divorced is by remarriage. However, children in remarriage families, especially girls who are related to stepfather, are not fulfilled their rights, which can be seen from the interactions that occur. This study aims to describe the pattern of interaction between girls and stepfather in Kijang Village, East Bintan District, Bintan Regency. This research was conducted with a qualitative approach with a descriptive type. Research informants were selected with purposive techniques as well as in data collection using observation techniques and in-dept interviews. The findings of this study are that self-indication is formed when a doughter interacts with a stepfather, namely the stepfather as a complement to the family and the stepfather as s surrogate figure. As for the process of approaching stepfather to children, there are two pattern, namely 1) introduced before marriage, and 2) not being introduced before marriage. Then the interaction that arises between the stepfather and their children is in the form of dinner together, accompanied when studying, watching television, pisking up school, holiday and visiting the step-family.